Physical examination in vascular problems. Part two - Mościcka, Paulina; Szewczyk, Maria Teresa; Cierzniakowska, Katarzyna; Cwajda-Białasik, Justyna; Popow, Aleksandra; Kozłowska, Elżbieta; Woda, Łukasz; Jawień, Arkadiusz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2013)
Vascular problems assume an important place in medicine as they affect millions of patients worldwide. Knowledge and ability to perform physical examination of the vascular system by a nurse are vitally important. Properly conducted physical examination of the vascular system can constitute the basis for accurate nursing diagnosis and intervention, e.g. implementation of preventive measures, care, or treatment. The aim of this paper is to present physical examination of the vascular system of the upper body: head, neck, upper limbs, and abdomen, as the basis for nursing diagnosis in patients with vascular problems.